2012
DOI: 10.1038/ejcn.2012.125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different types of fast food on postprandial metabolism in normal and overweight subjects

Abstract: A Ramel, FD Gudmundsdottir and I Thorsdottir BACKGROUND/OBJECTIVES: The aim was to investigate the effects of a conventional and an unconventional fast-food meal on postprandial metabolism in normal and in overweight subjects. SUBJECTS/METHODS: Twenty-five healthy normal (n ¼ 12) and overweight (n ¼ 13) volunteers (21-39 years) participated in this randomized, dietary cross-over study and received two test meals (matched in energy and energy giving nutrients) after an overnight fast with 1 week between test da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Dietary fibre, especially soluble, lowers blood sugar responses [145,146], and resistant starch has been shown to improve glucose metabolism and attenuate related inflammation in individuals with type 2 diabetes [147]. Meals based on fibre-rich rye sourdough bread, salmon, vinegar and vegetables, were associated with approximately 40% lower blood glucose and insulin responses, compared with a fast food/meal matched for energy and macronutrients [148]. A cross-over study in adults at risk for the metabolic/dysglycaemic syndrome showed whole grains to provide anti-inflammatory protection compared to refined grains, an advantage attributed in large part to fibre [149].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibre, especially soluble, lowers blood sugar responses [145,146], and resistant starch has been shown to improve glucose metabolism and attenuate related inflammation in individuals with type 2 diabetes [147]. Meals based on fibre-rich rye sourdough bread, salmon, vinegar and vegetables, were associated with approximately 40% lower blood glucose and insulin responses, compared with a fast food/meal matched for energy and macronutrients [148]. A cross-over study in adults at risk for the metabolic/dysglycaemic syndrome showed whole grains to provide anti-inflammatory protection compared to refined grains, an advantage attributed in large part to fibre [149].…”
Section: Resultsmentioning
confidence: 99%
“…Effect of lean red meat was similar to low-fat dairy protein [160]. However, a conventional beef hamburger meal showed significantly higher glycaemic and insulinemic response than a salmon burger meal despite both having similar glycaemic load [148]. Together, the evidence suggests that both plant [152,153] and animal proteins have the potential to reduce glycaemic response, especially when consumed in an early stage of the meal [161,162,163].…”
Section: Resultsmentioning
confidence: 99%
“… 26 Compared to a healthy fast food meal (fiber rich sourdough rye bread, salad with vinegar, orange juice), a hamburger meal (hamburger, bacon, cola drink) was associated with higher postprandial serum levels of glucose and insulin. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Un estudio realizado en una universidad de Lima Metropolitana, señala que el menú ofertado a los estudiantes no llega a cubrir ni el 50% del requerimiento de fibra para el almuerzo lo cual se considera subalimentación (29) . Además, el artículo publicado por Ramel, muestra que dos productos similares, pero preparados con ingredientes de mejor calidad nutricional tienen diferentes efectos en el organismo, siendo uno más beneficioso que otro y teniendo la misma palatabilidad (30) . Esto sugiere que se debería mejorar la calidad de los insumos utilizados en las ensaladas y las proporciones en los que estos son utilizados para mejorar el valor nutricional de estas (aumentar fibra, disminuir colesterol y priorizar el consumo de ácidos grasos esenciales y micronutrientes).…”
Section: Discussionunclassified